The Estimation of Technological Provision of Administrative Services by the Public Authoriries by the Donetsk Population - Perederiy, Maryna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article discusses the problem of the ambiguity of understanding the concept of «administrative services». The results of sociological research, which dealing with Donetsk citizens’ assessment of technological effectiveness in authority’s provision of administrative services has been emphasized represented by measures to improve the quality of these services. The results of this research have been presented in the article.